2022
DOI: 10.26529/cepsj.1426
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Technology in Educating English Language Learners at-risk or with Disabilities: A Systematic Review

Abstract: With the development of technology, the quantity and quality of electronic devices for students learning English as a second or foreign language (ESL/EFL) are on the rise, especially since the outbreak of the Covid-19 pandemic. To facilitate practices in English language education for students with special needs, the researchers conducted a systematic review of the empirical studies of technology tools for ESL/EFL students with learning difficulties published in the previous two decades. This paper presents th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…We have identified two similar systematic review studies (Fernández-Batanero et al, 2022;Jiang et al, 2022) performed on the same sample of learners that identified the best trends, practices, pedagogical implications, and limitations of AT of only VI learners. The studies confirmed that AT helped with the inclusion of disabled students, however, they also confirmed that teachers needed to be more trained and educated in the use of these devices when teaching disabled students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified two similar systematic review studies (Fernández-Batanero et al, 2022;Jiang et al, 2022) performed on the same sample of learners that identified the best trends, practices, pedagogical implications, and limitations of AT of only VI learners. The studies confirmed that AT helped with the inclusion of disabled students, however, they also confirmed that teachers needed to be more trained and educated in the use of these devices when teaching disabled students.…”
Section: Discussionmentioning
confidence: 99%
“…The positive impact of AT on learners' engagement and their academic success was confirmed in the review by Fernández-Batanero et al (2022) as well. Also, as Jiang et al (2022) suggest that assignments for disabled students should be tailored to their cognitive and language skills, they should build on the strengths of the students and should be in synchronicity with their individual requirements. The same is applied to the teachers who should be clear and concise in their instructions to this type of learner.…”
Section: Discussionmentioning
confidence: 99%